Programming in Ada 95 - Barnes, J. G. P. (John Gilbert Presslie) (Harlow : Addison-Wesley, 1998)
Written by a key member of the original Ada design team 'Programming in Ada 95' and its predecessor, 'Programming in Ada' have long been established as the definitive texts on Ada. Now John Barnes has revised and updated this classic book to enhance its value to both Ada newcomers and veteran Ada programmers alike. Ada 95 is the first fully object oriented language to become an ISO standard, its power and flexibility make it suited to a wide range of complex applications, from process control and industrial design to telecommunications and diagnostic analysis.This book provides complete tutorial coverage of all the core features of the language, illustrated throughout with extensive examples. Key Features x Six new examples of complete programs included as distinct chapters, with commentary x CD featuring special edition of ObjectAda compiler, including online Ada Reference Manual x More on overall program structure, child units and object oriented programming x Further detail on the predefined library x New edition also features a broader overview in the introductory chapters and further discussions of advanced topics such as storage pools and an extended index
This text and reference for programmers and students provides complete tutorial coverage of Ada 95. Illustrated with many complete programs, this edition highlights the power of object-oriented programming and the security of a modern software engineering language.
Ada is a programming language rich in capabilities for building software systems for general as well as defense purposes.
Introduction -- Simple Concepts -- Abstractions -- Programs and Libraries -- Part II: Algorothmic Aspects -- Scalar Types -- Control Structures -- Arrays and Records -- Subprograms -- Access Types -- Part III: The Big Pictures -- Packages and Private Types -- Overall Structure -- Object-Oriented Programming -- Exceptions -- Numeric Types -- Parameterized Types -- Generics -- Tasking -- Object-Oriented Techniques -- Part IV: Completing the Story -- Predefined Library -- Interfacing -- The Specialized Annexes.
Includes bibliographical references (p. 685-686) and index.
1
Keywords: Ada 95 (Computer program language)